IMPACT OF THE BRICS ON THE RUSSIAN ECONOMY AND TRADE - Mamadvalieva, Karina; 何枭吟, He Xiaoyin (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2024)
This study explores the influence of the BRICS nations on the Russian economy, with a specific focus on trade dynamics and their impact on Russia's Gross Domestic Product (GDP) growth. Through a comprehensive analysis spanning from 2011 to 2022, this study delves into the volume of trade between Russia and each BRICS country, assessing the stability, trends, and sectoral composition of these trade relationships. The study utilizes regression analysis to evaluate the correlation between Russia's economic indicators and its trade activity within the BRICS framework. The findings indicate a significant impact of trade with BRICS countries on Russia's economic performance, particularly highlighting the role of exports and imports in driving GDP growth. The research also forecasts Russia's GDP from 2023 to 2025, providing insights into the potential future economic trajectory based on trade patterns with BRICS nations. This study contributes to understanding the strategic importance of the BRICS alliance for Russia's economic landscape, suggesting that continued and diversified trade relations within this group could be key to Russia's economic prosperity.